2002
DOI: 10.1007/s00216-002-1352-5
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbent materials commonly used in air analysis for adsorptive enrichment and thermal desorption of volatile organic compounds

Abstract: A review is given dealing with commonly used adsorbent materials in ambient air analysis of volatile organic compounds (VOCs). The adsorbents covered in the paper are selected in consideration of their compatibility with thermal desorption. Initially, we discuss the requirements that an adsorbent should fulfill, and useful parameters for the selection and evaluation of an appropriate material. Then, the most important materials are presented considering their properties, advantages, and drawbacks. A few applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
174
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(180 citation statements)
references
References 74 publications
1
174
0
5
Order By: Relevance
“…Unfortunately, CMS are required for the quantitative adsorption of compounds that are more volatile than pentane and high polarity low-molecular-weight compounds [24,25]. The evaluation of a multibed trap without the presence of a CMS showed that some of the main components in breath samples (e.g., acetone, methanol, ethanol) cannot be adequately adsorbed when only graphitized carbons are present in the sorbent tube.…”
Section: Microtrap Evaluationmentioning
confidence: 99%
“…Unfortunately, CMS are required for the quantitative adsorption of compounds that are more volatile than pentane and high polarity low-molecular-weight compounds [24,25]. The evaluation of a multibed trap without the presence of a CMS showed that some of the main components in breath samples (e.g., acetone, methanol, ethanol) cannot be adequately adsorbed when only graphitized carbons are present in the sorbent tube.…”
Section: Microtrap Evaluationmentioning
confidence: 99%
“…The multisorbent configuration is not necessary, as the later sorbent layers do not contact compounds. Tenax TA is the most common sorbent due to its high thermal stability, low inherent artifacts and degradation, hydrophobicity and accommodation for wide volatility [29,30]. It also allows efficient desorption and displays optimal GC performance when used as a chromatographic stationary phase.…”
Section: Standard Atd Tubesmentioning
confidence: 99%
“…This problem can be resolved by the application of multibed adsorption tubes, packed in order of increasing sorbent strength to cover diverse analytes over a broad range of volatility and polarity [15,16]. Although limited under ambient conditions, a comprehensive review of different adsorbents available for the adsorptive enrichment and thermal desorption in ambient air analysis has been studied by Dettmer and Engewald [17].…”
Section: Selection Of Sorbents For Ctmentioning
confidence: 99%
“…Carboxen 1000 (60/80 mesh, CMS with SSA l1200 m 2 /g) is one of the strongest adsorbents for collecting light VOCs (C 2 -C 5 ) [7]. The CT (III) was prepared with Tenax TA (60/80 mesh, porous organic polymers with SSA l35 m 2 /g) suitable for the collection of heavy VOCs (C 7 -C 26 ) [17]. In fact, Tenax TA has been recommended by the ECA-IAQ working group for the determination of total VOC concentration [11].…”
Section: Selection Of Sorbents For Ctmentioning
confidence: 99%